Topical anesthesia therapy using lidocaine-loaded nanostructured lipid carriers: tocopheryl polyethylene glycol 1000 succinate-modified transdermal delivery system - Zhao X; Sun Y; Li Z (Dove Medical Press, 2018)
Xiangju Zhao, Ying Sun, Zhaoguo Li Department of Anesthesiology, Affiliated Hospital of Jining Medical University, Jining, Shandong 272000, People’s Republic of China Purpose: Transdermal drug delivery of local anesthetics using lipid nanoparticles could enhance lipophilic drugs permeation through the stratum corneum, improve drug diffusion to deeper skin, and exert good therapeutic effects. The purpose of this study was to engineer a Tocopheryl Polyethylene Glycol 1000 Succinate (TPGS)-modified cationic nanostructured lipid carriers (NLC) for the delivery of lidocaine (LID; TPGS/LID-NLC).Materials and methods: TPGS/LID-NLC was prepared by solvent diffusion method. The particle size, polydispersity index, zeta potential, drug entrapment efficiency, drug loading, stability, drug release, and cytotoxicity were tested to evaluate the basic characters of NLC. In vitro skin permeation and in vivo anesthesia effect in an animal model were further investigated to determine the therapeutic efficiency of the system.Results: TPGS/LID-NLC had a particle size of 167.6±4.3 nm, a zeta potential of +21.2±2.3 mV, an entrapment efficiency of 85.9%±3.1%, and a drug loading of 11.5%±0.9%. A sustained release pattern was achieved by TPGS/LID-NLC, with 81.2% of LID released at 72 hours. In vitro permeation study showed that the steady-state fluxes (Jss), permeability coefficient (Kp), and cumulative drug permeation Qn at 72 hours (Q72) of TPGS/LID-NLC were 15.6±1.8 µg/cm2/hour, 10.3±0.9 cm/hour (×10-3), and 547.5±23.6 µg/cm2, respectively, which were significantly higher than the nonmodified NLC and free drug groups. In vivo anesthesia effect of TPGS/LID-NLC was the most remarkable and long acting among the formulations tested, which could be concluded by the most considerable maximum possible effect from 10 to 120 minutes during the whole research.Conclusion: The most prominent in vitro permeation efficiency and in vivo anesthetic effect of TPGS/LID-NLC could be the evidence that TPGS-modified NLC could function as a promising drug delivery system for prolonged and efficient local anesthetic therapy. Keywords: local anesthetics, transdermal delivery, tocopheryl succinate, nanostructured lipid carriers, lidocaine